EFEKTIVITAS MEDIA PUZZLE OF PARAGRAPH STORY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Sulistyani, Guritno; Ichda Wahyuni, Holy; Nanda Faradita, Meirza (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This research is motivated by students who find it difficult to remember and understand the material on the role of the figures in the struggle to defend Indonesia because the chronology of events and time are very past. Based on this, this study aims to determine the effectiveness of the puzzle of paragraph story media to improve student learning outcomes in social studies learning in elementary schools. This type of research uses experiments with quantitative research methods. The sampling technique in the study is the purposive sampling technique. The results of this study show that the learning outcomes of students in the control class have an average of 51.4, the experimental class has an average of 42.0. From the data, it is known that the experimental pre-test score is lower than the control pre-test. In the results of this study after the puzzle of paragraph story media was applied to the experimental class, it was found that the average post-test was 82.1. The results of the study showed that the use of puzzle of paragraph story media was proven to be effective in social studies learning on student learning outcomes.